Repurposing of Glycine-Rich Proteins in Abiotic and Biotic Stresses in the Lone-Star Tick (Amblyomma americanum) - Bullard, Rebekah; Sharma, Surendra Raj; Das, Pradipta Kumar; Morgan, Sarah E.; Karim, Shahid (Frontiers in Physiology, 2019)
Tick feeding requires the secretion of a huge number of pharmacologically dynamic proteins and other molecules which are vital for the formation of the cement cone, the establishment of the blood pool and to counter against the host immune response. Glycine-rich proteins (GRP) are found in many organisms and can function in a variety of cellular processes and structures. The functional characterization of the GRPs in the tick salivary glands has not been elucidated. GRPs have been found to play a role in the formation of the cement cone; however, new evidence suggests repurposing of GRPs in the tick physiology. In this study, an RNA interference approach was utilized to silence two glycine-rich protein genes expressed in early phase of tick feeding to determine their functional role in tick hematophagy, cement cone structure, and microbial homeostasis within the tick host. Additionally, the transcriptional regulation of GRPs was determined after exposure to biotic and abiotic stresses including cold and hot temperature, injury, and oxidative stress. This caused a significant up-regulation of AamerSigP-34358, Aam-40766, AamerSigP-39259, and Aam-36909. Our results suggest ticks repurpose these proteins and further functional characterization of GRPs may help to design novel molecular strategies to disrupt the homeostasis and the pathogen transmission.